EARLY-LIFE INFLUENCES ON MID- AND LATER-LIFE WELL-BEING: NEW EVIDENCE FROM THE NLSY79. (11th November 2018) - Carr, D; Groen, J; Burgard, S
Abstract: Mounting research underscores the importance of early social background factors, education, work and family trajectories, and wealth acquisition for health and well-being in later life. These explorations require prospective multiwave data to delineate causal mechanisms. This panel presents research based on the National Longitudinal Survey of Youth 1979 (NLSY79), which has followed a cohort of men and women from their adolescent years through their early 60s, across 27 data waves. Walsemann shows how educational attainment and the timing of degree completion shapes smoking trajectories. Harrati et al. document how unemployment trajectories affect risk of cancer, hypertension, diabetes, and depression at age 50. Aughinbaugh et al. examine wealth acquisition over the life course and its health implications; 15 percent of NLSY79 midlife adults have negative net worth, which is linked with poorer self-rated health. Umberson et al. show how blacks' elevated risk of spousal, parental, and child bereavement account in part for race disparities in midlife physical health. The discussants underscore the importance of considering complex life course trajectories as influences on the timing and onset of health conditions, pointing out sites of intervention for policy and practice. The papers also demonstrate the rich potential for the NLSY79 to make novel contributions to our understanding of the aging processes of late Baby Boomers.